Adaptive stabilization of uncontrolled rectifier based AC-DC power systems feeding constant power loads - Areerak, Kongpan; Sopapirm, T.; Bozhko, Serhiy; Hill, Chris; Suyapan, A.; Areerak, Kongpol (IEEE, 2017)
It is known that, when tightly regulated, actively controlled power converters behave as constant power loads (CPLs). These loads can significantly degrade the stability of their feeder system. The loop-cancelation technique has been established as an appropriate methodology to mitigate this issue within dc–dc converters that feed CPLs. However, this has not yet been applied to uncontrolled rectifier based ac–dc converters. This paper therefore details a new methodology that allows the loop-cancelation technique to be applied to uncontrolled rectifier based ac–dc converters in order to mitigate instability when supplying CPLs. This technique could be used in both new applications and easily retrofitted into existing applications. Furthermore, the key contribution of this paper is a novel adaptive stabilization technique, which eliminates the destabilizing effect of CPLs for the studied ac–dc power system. An equation, derived from the average system model, is introduced and utilized to calculate the adaptable gain required by the loop-cancelation technique. As a result, the uncontrolled rectifier based ac–dc feeder system is always stable for any level of CPL. The effectiveness of the proposed adaptive mitigation has been verified by small-signal and large-signal stability analysis, simulation, and experimental results.